STUDI KOMPARASI PEMBELAJARAN SENI LUKIS PADA EKSTRAKURIKULER DI SD IT AZ-ZAHRA DAN SD NEGERI BINTORO 04 KABUPATEN DEMAK - Ana Rofatul Lutfiyah; Rofian Rofian; Prasena Arisyanto (FKIP, PGSD, Universitas Slamet Riyadi, 2020)
This research aims to find out the management management system, administration and extracurricular learning of painting art at SD IT Az-Zahra and SD N Bintoro 04 in encouraging the success of learners in the competition